YELLOW ISLAMIC CLASSIC BOOK LEARNING MODEL BASED ON INFORMATION AND COMMUNICATION TECHNOLOGY IN PESANTREN - Santoso Ariyadi, Moh; Fauzi, Ahmad; Inzah, M. (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Learning yellow books in Islamic boarding schools is one of the main pillars in strengthening the tradition of classical Islamic knowledge. However, the challenges of the digital era require innovation in learning methods, including the integration of information and communication technology (ICT). This study aims to examine and develop an ICT-based yellow book learning model that is in accordance with the characteristics of Islamic boarding schools. This study uses a qualitative approach with the type of research applied being library research. Data collection techniques include observation, in-depth interviews, and documentation, which are analyzed thematically. The results of the study indicate that the use of ICT, such as digital interpretation applications, PDF versions of yellow books, and online learning platforms, can increase the effectiveness of students' understanding of the contents of the book, accelerate the learning process, and facilitate interactive discussions between teachers and students. However, the success of implementing this model is highly dependent on the readiness of infrastructure, digital competence of teachers, and support from Islamic boarding school policies. This study recommends the development of an ICT-based adaptive curriculum and continuous teacher training as part of the digital transformation of Islamic boarding schools.